New Insights Into the Anticonvulsant Effects of Essential Oil From Melissa officinalis L. (Lemon Balm) - Chindo, Ben A.; Howes, Melanie-Jayne R.; Abuhamdah, Sawsan; Yakubu, Musa I.; Ayuba, Godwin I.; Battison, Alex; Chazot, Paul L. (Frontiers in Pharmacology, 2021)
Melissa officinalis L. is used in traditional European and Iranian folk medicines to manage a plethora of neurological diseases including epilepsy. In this study, we utilized the in vitro and in vivo models of epilepsy to probe the anticonvulsant potentials of M. officinalis essential oil (MO) to gain insight into the scientific basis for its applications in traditional medicine for the management of convulsive disorders. MO was evaluated for effects on pentylenetetrazole (PTZ) and maximal electroshock (MES)-induced seizures in mice, on brain slice 4–aminopyridine (4-AP) model of epilepsy and sustained repetitive firing of current clamped neurons; and its ameliorative effects were examined on seizure severity, anxiety, depression, cognitive dysfunction, oxidative stress and neuronal cell loss in PTZ-kindled rats. MO reversibly blocked spontaneous ictal-like discharges in the brain slice 4-AP model of epilepsy, and secondary spikes produced by sustained repetitive firing in current clamped neurons, suggesting anticonvulsant effects and voltage-gated sodium channel blockade. MO protected mice from PTZ– and MES–induced seizures and mortality, and ameliorated seizure severity, fear-avoidance, depressive-like behavior, cognitive deficits, oxidative stress and neuronal cell loss in PTZ–kindled rats. The findings warrant further study for the potential use of MO and/or its constituent(s) as adjunctive therapy for epileptic patients.